SERIAL ESTIMATION OF CA 15.3 CAN PREDICT THE OUTCOME IN PATIENTS WITH BREAST CANCER – A PROSPECTIVE STUDY. - SOUMI SAHA; DR. VIKAS SINGH; DR. SUVRO GANGULI; DR. SOUMEN DAS; DR. SHYAMSUNDAR MANDAL; DR. DIPTENDRA K SARKAR (International Journal of Pharma and Bio Sciences, 2014)
CA 15.3 is widely applied for long term follow-up and monitoring therapy of breast cancer patients. The present study was conducted to assess the role of CA 15.3 in association with Nottingham Prognostic Index (NPI) to detect outcomes of breast cancer patients. Blood samples were collected from 85 nonmetastatic breast cancer patients and 57 patients with benign breast disease (BBD). CA 15.3 was measured from serum by ELISA. By comparing pre and post op CA 15.3 level, a significant decline in post op values were observed in majority of patients. NPI scores of patients were calculated. 18-24% of patients who had persistently elevated CA 15.3 in post-op follow-up and scored NPI>5.4, showed PO in term of recurrence/relapse/distant metastasis. Also PO (NPI>5.4) was correlated with large TS, different grades and with nodal metastasis. Raised post-op CA 15.3 along with high NPI can be predictive to derive outcome in breast cancer patients.